Oncogenic osteomalacia: role of Ga-68 DOTANOC PET/CT scan in identifying the culprit lesion and its management - Singh, Deepa (Br J Radiol, 2017)
OBJECTIVE: The aim of this study was to evaluate the role of (68)Ga-DOTANOC positron emission tomography (PET)/CT scan in localization of culprit lesion for biopsy and required intervention [surgical excision/radiofrequency ablation (RFA)] in patients with long-standing oncogenic osteomalacia (OOM)/tumour-induced osteomalacia. METHODS: 17 patients (8 males and 9 females) underwent (68)Ga-DOTANOC PET/CT scan. The patients referred with clinical and biochemical evidence of hypophosphatemia and raised fibroblast growth factor-23. Qualitative and semi-quantitative parameters were used to identify culprit lesions. RESULTS: (68)Ga-DOTANOC PET/CT scan revealed 52 lesions in 17 patients, and 37/52 of these lesions were tracer avid. 26/37 lesions were non-specific focal tracer-avid skeletal lesions (fractures or degenerative changes). 11/37 tracer-avid skeletal lesions present in 9 patients (3 lesions in 1 patient and 1 each in rest of the 8 patients) were highly suspicious for culprit lesions in view of high maximum standardized uptake value (SUV(max)) (range 1.5–15.4; mean 7.0 ± 4.6), lesion size (0.9–5.0 cm; mean 3.3 ± 1.5) and associated soft-tissue component. During subsequent imaging with CT/MRI, 7/9 patients showed concordant lesions which were excised or biopsied and histopathologically verified as phosphaturic mesenchymal tumours. Surgical excision was resorted to in most of the detected lesions, and RFA was performed in one patient. CONCLUSION: There is some overlap in SUV(max) between fracture-/bone-associated lesions and culprit lesions with a tendency of most non-culprit lesions to have lower SUV(max) and no associated soft-tissue component. In such scenario, intensely tracer-avid, larger non-fracture lesions with soft-tissue component may lead to identification of culprit lesion among multiple lesions. Following detection of culprit lesion, surgical removal is the best treatment. RFA is alternative to surgery in cases where surgery is not possible owing to osteopenia/poor bone health. ADVANCES IN KNOWLEDGE: The main challenge in patients of long-standing OOM is the presence of multiple skeletal lesions (both tumour- or tracer-avid fractures), and it is confusing to identify culprit lesion. This was noted in our study with (68)Ga-DOTANOC and has not been mentioned in studies performed with (68)Ga-DOTATATE/TOC PET/CT. In such scenario, (68)Ga-DOTANOC PET/CT needs to be reviewed and read thoroughly to localize the culprit lesion out of the multiple tracer-avid lesions.